2000
DOI: 10.1258/002367700780384726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of assays for antibodies to Encephalitozoon cuniculi in rabbits

Abstract: SummaryTwo indirect immunofluorescence (IIF)assays, two enzyme-linked immunosorbent assays (ELISAs)and the carbon immunoassay (CIA)for determination of antibodies to Encephalitozoon cuniculi were compared using 210 sera of rabbits, 135 of which originated from seven infected colonies, while 75 originated from four uninfected colonies. There was no evidence of a difference between the different assays with respect to the number of positive sera. There was a clear correlation between the quantitative response me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Table 1 shows the prevalence values according to the two diagnostic assays used, and according to the clinical signs of the tested rabbits. It should be noted that there were no differences in the number of positive sera detected by the ELISA and the CIA tests as also reported by Boot et al. (2000).…”
Section: Resultssupporting
confidence: 78%
“…Table 1 shows the prevalence values according to the two diagnostic assays used, and according to the clinical signs of the tested rabbits. It should be noted that there were no differences in the number of positive sera detected by the ELISA and the CIA tests as also reported by Boot et al. (2000).…”
Section: Resultssupporting
confidence: 78%
“…Specific antibodies develop within 21 days post-infection (11,33). In clinically healthy rabbits, the present study showed that the seropositivity rate for E. cuniculi infection was 49.5%, which is similar to rates (50-53%) of infection in previous studies (6,14,20), although it is higher than the rates of infection reported in some (4,13,17,26,28,(30)(31)(32). In contrast, in the current study, the seropositivity rate of the disease was lower than those previously reported (71-93%) in various countries (3,10,21,37).…”
Section: Discussionsupporting
confidence: 85%
“…Various diagnostic tests have been developed in order to detect antibodies to E. cuniculi and all are suitable for the use in rabbits. Indirect fluorescent antibody technique (IFAT) and ELISA are the most common tests and correlate well with each other (Boot et al 2000;Jordan et al 2006). Serological screening is used by laboratories to identify and cull potentially infected animals to reduce interference with experimental results (Pakes and Gerrity 1994).…”
Section: Serologymentioning
confidence: 98%